PERJANJIAN EKSTRADISI DALAM PENEGAKAN HUKUM TINDAK PIDANA KORUPSI DI INDONESIA - Rona Sahati, Nabella; Alam, Kodrat (Yustitia, 2020)
Extradition Agreeament (treaty) provides facilities for countries that have an agreement, where the agreement is to act against, arrest and prosecute criminals in a country who have fled to another country outside national jurisdiction. The presence of the perpetrator in another country is to avoid attempts to arrest him in connection with the crime he has committed in the country of origin. So by running out of the country, this means that there are other countries whose interests are harmed because they cannot arrest the perpetrator, in which the perpetrator has committed a violation of the law based on the location where the crime was committed (locus delicti). One of them is that the criminal case of corruption is considered a threat of extraordinary crime that harms all people in the world, in upholding the law of corruption in which the perpetrator has fled abroad so that he feels safe and free from a crime he has committed. So extradition is very necessary for the perpetrators of corruption who have fled to other countries. From the background that has been explained, the following problems can be made inventory, namely 1) what is the position of the extradition agreement in international law related to criminal acts of corruption and 2) how is the implementation of extradition agreements against perpetrators of corruption in Indonesia. This study uses a normative juridical research method, namely legal research that refers to legal norms contained in statutory regulations with descriptive analytical research specifications with the aim of obtaining an overview of the application of extradition agreements to perpetrators of corruption in Indonesia based on Law Number 1 of 1979 of Extradition. The results in this research have shown that indeed there have been regulations regarding extradition treaties but it has been long enough and it is necessary to have regulatory reforms according to existing needs, furthermore it is necessary to improve diplomatic relations because law enforcement of criminal acts of corruption which involves cooperation between two countries is not only achieved through extradition treaties, but also good diplomatic relations.